SISTEM PEMANAS AIR ENERGI SURYA MENGGUNAKAN KOLEKTOR PALUNG PARABOLA POSISI TIMUR-BARAT - Martha Rianna; Maksi Ginting; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Heating System of Solar Energy by using Parabolic Trough Collector of East West Position has been experimentally conducted. The collector is set at open air from the sun radiation and observed every 60 minutes from 9 AM until 3 PM for bright sunshine. After 14 days, the results show that the collector temperature has a minimum average of collector 40,290C and water tank 36,070C at 10 AM, whereas the highest average temperature is 51,260C and water tank 45,570C at 1 PM. The observation describes the highest temperature at collector tank occurs at 1 PM due to the highest radiation intesity to the collector reaching maximum value of 448 W/m2. Loss heat by conduction at lowest rate is 23,50 J/s at 10 AM whereas loss heat by conduction at highest rate 36,60 J/s at 1 PM. The average water volume is 39 liters for 6 hours daily from 9 AM until 3 PM. Overall, the higher radiation intensity from the sun to heat the collector, the higher water temperature observed in the collector tank.